75th Anniversary of the Geneva Conventions, 1949 and the Rights of the Children During Armed Conflict: An Analysis - Taak, Sangeeta (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
2024 marks the 75th anniversary of the four Geneva Conventions of 1949, providing an opportunity to reflect on their fundamental role in protecting people affected by armed conflict. There is a need to limit the means and methods of warfare. The underlying logic is that armed conflicts are triggered between states or among individuals. According to Jean Jacques Rousseau, "War is between the states. It has nothing to do with the individuals." Various international legal instruments have been adopted for the protection of civilians, including children and women. However, the protection guaranteed in these instruments is often violated by the occupying power or enemy combatants/forces. The paper hypothesizes that violations of the Geneva Conventions are frequent during armed conflict and must be addressed strictly. In this paper, an attempt has been made to explain the need to protect the rights of children during both non-international and international armed conflict. Secondly, the research delves into the pertinent question of whether the recruitment of children should be considered a violation of child rights. Thirdly, the paper seeks to hold perpetrators accountable for the violations of children's rights during armed conflict.